Tactical performance analysis in soccer by measuring inter -player coordination - Lemmink, K. A. P. M.; Frencken, W. G. P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Tactical match performance addresses the quality of actions of individual players or teams in space and time during match-play in order to be successful. In recent years, several approaches have been used to analyze tactical behaviour of players. Technological innovations have led to new possibilities to capture accurate spatio-temporal information of all players and unravel the dynamics and complexity of a soccer match. This lecture will focus on interactive behaviour of soccer teams or clusters of soccer players, f.e. midfielders, in full-sized matches (11 vs 11). It appears that small-sided games and full-sized matches adhere to and exhibit traits of dynamical systems. Based on positional match data interactive behaviour of teams or clusters of `active` players will be evaluated by calculating geometrical configurations, like centroids, surface areas, stretch indices and length per width ratios of both teams and relate them to each other. Variability in these inter-team measures obtained for different time windows will be mapped to match events using qualitative video analysis. Besides, critical events during the soccer match, like goal-scoring opportunities and goals, will be analyzed from this perspective.